"I feel hard...": an exploration of physical health experience among caregivers in providing care of stroke-survivors./ Dk Noor Azzatun N. A . Sobudin and Noor Amiera Alias - N. A . Sobudin, Dk Noor Azzatun; Alias, Noor Amiera (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
As the prevalence of stroke survivors is increasing each year, the demands among caregivers are also increasing where the stroke patients tend to rely on the help of caregivers to fulfil their daily needs. The increasing demands from the stroke survivors cause the caregivers at high risk of having the physical effects of caregiving. The study aims to explore the caregivers' experience in taking care of stroke survivors who live in rural areas. This is a phenomenological study on three caregivers of stroke survivors living in a rural area located in Sabah. By using Interpretative Phenomenological Analysis (IPA), a theme emerged which is "I feel hard ..." in relation to body pain, muscle soreness, reduce in physical performance and fatigue. It can be concluded that there are negative physical effects of taking care of stroke survivors among caregivers living in rural areas.